Naringenin glucuronidation in liver and intestine microsomes of humans, monkeys, rats, and mice. (January 2018) - Isobe, Takashi; Ohkawara, Susumu; Ochi, Sadayuki; Tanaka-Kagawa, Toshiko; Jinno, Hideto; Hanioka, Nobumitsu
Abstract: Naringenin, a flavanone found in citrus fruits, is mainly metabolized into glucuronide(s) by UDP-glucuronosyltransferase (UGT) enzymes in mammals. In the present study, the glucuronidation of naringenin in the liver and intestine microsomes of humans, monkeys, rats, and mice was examined. The kinetics of 7-glucuronidation in human liver and intestine microsomes followed the Michaelis-Menten model. Kinetics in mouse liver and intestine microsomes also followed the Michaelis-Menten model, whereas those in monkey and rat liver microsomes fit the biphasic model. Kinetics in monkey and rat intestine microsomes fit the Michaelis-Menten and substrate inhibition models, respectively. CLint values were mice > monkeys > rats > humans for liver microsomes, and mice > rats > monkeys > humans for intestine microsomes. In 4´-glucuronidation, activities in human liver microsomes and monkey liver and intestine microsomes were negligible or very low. Kinetics in rat and mouse liver microsomes followed the biphasic and Michaelis-Menten models, respectively. CLint values were rats > mice for liver microsomes, and rats > mice > humans for intestine microsomes. These results suggest that the metabolic abilities and regioselectivity of UGT enzymes toward naringenin in the liver and intestines generally differ between primates and rodents. Highlights: Naringenin regioselective glucuronidation in mammals were examined in vitro system. Hepatic 7-glucuronidation activities were mice > monkeys > rats > humans. Intestinal 7-glucuronidation activities were mice > rats ≥ monkeys > humans. Heapatic 4′-glucuronidation activities were mice > rats > humans >> monkeys. Intestinal 4′-glucuronidation activities were mice > rats >> humans and monkeys.